Analisis Foto Udara dengan Multicopter di Daerah Penghasil Pasir Besi Karangwuni, Temon, Kulon Progo - Indreswari Suroso (Institut Seni Indonesia Yogyakarta, 2020)
Aerial Photo Analysis Using Multicopters in the Iron-Sand Producing Area in Karangwuni, Temon, Kulon Progo. This research was conducted in areas that have the potential for iron-sand, which is in Karangwuni village, Temon Subdistrict, Kulon Progo regency. The aim of this research is to examine the surface of the largest iron-sand producing areas in Kulon Progo. The specifications of the drones used in this research are as follows: frame :F450Flight Control: DJI Naza M-Lite; Propeller: 1045 Prop; Motorcycle: brushless sunnsky 980 kVa; ESC: Skywalker 40 Ampere 3s; Battery: Ace 3s Gens 5000mAH; Remote: Turnigy 9XR together with Frsky Tanseiver; and Camera: Xiaomi Yi 4k international edition. The drone made the mapping by recording the surface of the area. Once the drone was assembled, it was tested to fly. When the drone has flown perfectly, a camera was added on the lower side. So, the image of the surface were mapped using the camera which was attached to the drone. Before mapping the area using the drone, drone was tested again. The initial step of assembling was to choose the component. The drone could fly up to 70 meters until 100 meters with a duration up to 10 minutes using the payload drone multicopter weighed 1.5 kilograms. The result of this aerial photo analysis on mapping the largest iron-sand producing area in Kulon Progo regency showed that the area mapped are very sandy and very arid, therefore it cannot be used for an agricultural land. The government of Kulon Progo regency sets a regulation that this area could be used as an iron-sand mining because this land is no longer suitable for an agricultural land as in previous times. ABSTRAKPenelitian ini dilakukan di daerah yang memiliki potensi pasir besi, yaitu di daerah Karangwuni, Kecamatan Temon, Kabupaten Kulon Progo. Tujuan penelitian ini adalah untuk meneliti permukaan wilayah daerah penghasil pasir besi terbesar di Kulon Progo. Spesifikasi drone yang digunakan penelitian ini adalah dengan spesifikasi frame: F450; pengendali penerbangan: DJI Naza M-Lite; propeller: 1045 Prop; sepeda motor: brushless sunnsky 980 kVa; ESC: Skywalker 40 Ampere 3s; baterai: Ace 3s Gens 5000mAH; remote: Turnigy 9XR dengan Frsky Tanseiver; dan kamera: Xiaomi Yi 4k edisi Internasional. Cara drone melakukan pemetaan adalah dengan merekam gambar permukaan wilayah. Drone selesai dirakit, lalu diuji terbang. Jika drone telah terbang dengan sempurna, dilanjutkan dengan penambahan kamera di sisi bawah. Gambar permukaan area menggunakan kamera yang dipasang pada drone. Sebelum memetakan dengan drone, drone terlebih dahulu diuji lagi. Tahap awal perakitan adalah pemilihan komponen. Drone ini memiliki ketinggian dari 70 hingga 100 m dengan durasi hingga 10 menit menggunakan payload drone multicopter 1,5 kg. Drone ini menggunakan kamera DJI Naza M-Lite sehingga drone dapat memotret area seluas 1,5 km. Hasil penelitian foto udara pada pemetaan di daerah penghasil pasir besi terbesar di Kulon Progo ini adalah ternyata daerah tersebut berpasir dan sangat gersang sehingga tidak dapat dijadikan lahan pertanian. Pemerintah Kulon Progo memberikan izin untuk penambangan pasir besi dikarenakan lahan ini sudah tidak cocok untuk lahan pertanian seperti dahulu lagi.